Applications of Green Chemistry Approaches in Environmental Analysis - Yayayürük, Aslı E.; Yayayürük, Onur (Current Analytical Chemistry, 2019)
Background: Green chemistry is the application of methodologies and techniques to reduce the use of hazardous substances, minimize waste generation and apply benign and cheap applications. Methods: In this article, the following issues were considered: greener solvents and reagents, miniaturization of analytical instrumentation, reagent-free methodologies, greening with automation, greener sample preparation methods, and greener detection systems. Moreover, the tables along with the investigated topics including environmental analysis were included. The future aspects and the challenges in green analytical chemistry were also discussed. Results: The prevention of waste generation, atomic economy, use of less hazardous materials for chemical synthesis and design, use of safer solvents, auxiliaries and renewable raw materials, reduction of unnecessary derivatization, design degradation products, prevention of accidents and development of real-time analytical methods are important for the development of greener methodologies. Conclusion: Efforts should also be given for the evaluation of novel solid phases, new solvents, and sustainable reagents to reduce the risks associated with the environment. Moreover, greener methodologies enable energy efficient, safe and faster that reduce the use of reagents, solvents and preservatives which are hazardous to both environment and human health.
Keywords: miniaturization